Behavioural and neural correlates of auditory attention - Roberts, Katherine Leonie (2005)
The auditory attention skills of alterting, orienting, and executive control were assessed using behavioural and neuroimaging techniques. Initially, an auditory analgue of the visual attention network test (ANT) (FAN, McCandliss, Sommer, Raz, & Posner, 2002) was created and tested alongside the visual ANT in a group of 40 healthy subjects. The results from this study showed similarities between auditory and visual spatial orienting. An fMRI study was conducted to investigate whether the similar behavioural measures of auditory and visual executive control were the result of common cortical mechanisms. The results were consistent with a supramodal anterior network involved in conflict monitoring and resolution. Auditory orienting of attention was investigated through a series of behavioural experiments. The first investigated listeners' ability to benefit from cues to location, to pitch, and to both location and pitch, in a vowel-identification task. Subjects were able to benefit from all three types of cues but did not gain additive benefit from being cued to both location and pitch, suggesting that attention was being directed to an auditory object comprising both features. The following seven experiments investigated auditory spatial orienting in non-spatial tasks. These experiments revealed a robust exogenous (automatic) auditory orienting effect, which was relatively insensitive to task differences. However, endogenous (voluntary) auditory orienting effects were small and highly variable across subjects. It is hypothesised that differences between auditory and visual spatial orienting reflect the relative importance of spatial information in the two modalities, and differences in the neural coding of auditory and visual spatial information.